Effect of myringotomy as an office procedure on the clinical course of acute otitis media: a retrospective study - Andrews, Chakramakal Joseph; Rahul, Raveendran Krishnan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: A retrospective study was conducted to find out the effect of office myringotomy on clinical course of acute otitis media (AOM). Methods: Patients with signs and symptoms of AOM who underwent office myringotomy were included in the study. The clinical course such as pain, blocked sensation, relief of blocked feeling, hearing improvement, fever, discharge and residual perforation (5 and 14 days) were evaluated after the office myringotomy and compared. Results: Total 20 patients (10 females and 10 males of age between 5 to 30) were included in study. Among the total patients 12 were below <18 years age and remaining were above 18 years. The overall morbidity of these patients such as pain, blocked sensation and discharge was reduced after the office myringotomy. Furthermore, the residual perforation was absent during the end of 2nd week of post myringotomy. No discharge was found after the myringotomy. Conclusions: Simple myringotomy with five day course of antibiotic provides more symptomatic relief. The overall morbidity was less after the procedure. This indicates the requirement of myringotomy as an outpatient procedure in suitable patients.